Redox signalling involving NADPH oxidase-derived reactive oxygen species. (25th October 2006) - Dworakowski, R.; Anilkumar, N.; Zhang, M.; Shah, A.M.
Abstract : Increased oxidative stress plays an important role in the pathophysiology of many diseases such as atherosclerosis, diabetes mellitus, myocardial infarction and heart failure. In addition to the well-known damaging effects of oxygen-free radicals, ROS (reactive oxygen species) also have signalling roles, acting as second messengers that modulate the activity of diverse intracellular signalling pathways and transcription factors, thereby inducing changes in cell phenotype. NADPH oxidases appear to be especially important sources of ROS involved in redox signalling. Seven NADPH oxidase isoforms, known as Noxs (N APDH ox idases), are expressed in a cell- and tissue-specific fashion. These oxidases are thought to subserve distinct functions as a result of their tightly regulated activation (e.g. by neurohormonal and growth factors and mechanical stimuli) and their specific coupling with distinct downstream signalling pathways. In the present paper, we review the structure and mechanisms of activation of NADPH oxidases and consider their involvement in redox signalling, focusing mainly on the cardiovascular system.